Technical Efficiency and its Implications on Environmental Resources: The case of Small-Holders’ Maize Production in the Rufiji Basin, Tanzania - Lokina, Razack; Kulindwa, Kassim; Hepelwa, Aloyce (Tanzania Journal for Population studies and Development, 2009)
Agricultural land expansion in Tanzania, like in many other developing countries, is spurred by poor intensification of agriculture, where the use of irrigation and fertilizer is low, or sometimes applied inappropriately. Poor agricultural intensification and development in turn means pressure to convert forests and other marginal land to crop production in the quest to meet food and cash requirements. Using technical efficiency (TE) production frontier, this study empirically analyses agricultural productivity in Rufiji Basin. Identification of TE in agricultural production can be helpful for policy making aimed at finding ways to increase efficiency, and at the same time conserving environmental resources. The findings are that, estimated mean TE of maize is around 41% implying that there was substantial technical inefficiency in maize farming in Rufiji Basin. This would suggest that there are exists 59% potential for increasing maize yield at the existing level of their resources, and therefore reducing the pressure on forest resources by rural households in Rufiji basin. The relevant factors for improving technical efficient include household farming experiences, sex, religion, and household involvement in other occupations.